363P A randomized controlled trial of mindfulness breathing exercise in patients with advanced lung cancer - Ng, Diana Leh-Ching; Chai, Chee Shee; Tan, S. B.; Liam, Chong Kin; Pang, Y. K. (Oxford University Press, 2018)
Background: Study of mindfulness breathing exercise in dyspnea reduction of patients with advanced lung cancer is lacking.